The Link Between Communication And Conflict: A Review Of Four Paradigms - Putra, Aditya (Entrepreneurship Undergraduate Program at Amkop Business School, 2024)
Conflict is a universal condition within human groups. It manifests itself in economic distinctions (not differences), social change, cultural formation, psychological development and political organization, and then becomes evident through groupings of conflicting groups2; Who can have or be perceived as such, and goals that are incompatible with one another. Conflict is also dynamic, can increase or decrease, and is composed by a complex crossover between attitude (mental) and behavior (real), which can then construct its own reality or reality that can be different from the actual reality. So far, conflicts are often considered to occur due to communication failures, and thus there is an assumption that communication is a powerful remedy in overcoming conflicts. But in reality it is not that simple. This paper will examine why communication cannot be considered as the single most effective conflict resolution, using the 4 paradigms of communication approach.Keywords: conflict, communication, communication paradigm